UJI EFEKTIVITAS SERUM EKSTRAK DAUN KELOR (Moringa oleifera L.) SEBAGAI ANTIJERAWAT Staphylococcus aureus - Dewi, Bheta Sari; Werawati, Ayu; Hasanah, Uswatun; Sayyidah, Sayyidah; Dewantoro, Agung; Saputra, Aldi (Edu Masda Journal, 2025)
ABSTRACTAcne is among the most prevalent dermatological issues caused by the bacterium Staphylococcus aureus. Moringa leaf extract (Moringa oleifera L.) is known to contain bioactive compounds such as flavonoids, tannins, and alkaloids, which serve as anti-acne agents. This research seeks to assess the efficacy of a serum formulated with moringa leaf extract in inhibiting the growth of acne-causing Staphylococcus aureus. The extraction of moringa leaves was carried out using the maceration technique with 96% ethanol serving as the solvent. The extract was then formulated into a serum preparation with concentrations of 4%, 7%, and 10%, using Clindamycin as the positive control and the serum base as the negative control. The antibacterial efficacy was evaluated through the agar well diffusion technique to determine the inhibition zone against Staphylococcus aureus. Each treatment was conducted in triplicate. Additionally, the physical stability of the serum was assessed, covering organoleptic characteristics, homogeneity, pH, spreadability, and adhesion. The findings revealed that moringa leaf extract exhibited inhibitory effects on the growth of Staphylococcus aureus, as evidenced by the presence of inhibition zones. The inhibition zone diameters were 14.21 mm at 4% concentration, 17.30 mm at 7%, and 19.20 mm at 10%. In comparison, the positive control showed a diameter of 30.78 mm, while the negative control showed no inhibition (0 mm). This research suggests that serum formulated with moringa leaf extract holds promise as an effective topical solution for treating acne.                                                  ABSTRAKJerawat ialah satu diantara masalah kulit yang umum disebabkan oleh bakteri Staphylococcus aureus. Ekstrak daun kelor (Moringa oleifera L.) dikenal punya senyawa bioaktif seperti flavonoid, tanin, dan alkaloid sebagai agen antijerawat. Kajian ini memiliki tujuan guna melakukan uji efektivitas serum berbahan dasar ekstrak daun kelor dalam menghambat pertumbuhan bakteri jerawat Staphylococcus aureus. Ekstrak daun kelor diperoleh lewat metode maserasi dengan pelarut etanol 96%. Ekstrak ini kemudian diformulasi ke sediaan serum dengan konsentrasi 4%, 7%, dan 10% serta digunakan Clindamycin sebagai kontrol positif dan basis serum menjadi kontrol negatif. Uji aktivitas antibakteri memakai metode difusi sumuran agar, guna mengukur zona hambat pada Staphylococcus aureus. Perlakuan diulang sebanyak 3 kali. Stabilitas fisik serum juga diuji meliputi organoleptis, homogenitas, pH, daya sebar dan daya lekat. Hasilnya diperoleh bahwa ekstrak daun kelor mempunyai kemampuan menghambat pertumbuhan Staphylococcus aureus bisa diamati dengan adanya zona hambat yang dibentuk. Diameter zona hambat di konsentrasi 4% senilai 14,21 mm, konsentrasi 7% sebesar 17,30 mm, konsentrasi 10% senilai 19,20 mm, kontrol positif senilai 30,78 mm, dan kontrol negatif sebesar 0 mm. Kajian ini memberi indikasi jika serum ekstrak daun kelor punya potensi jadi sediaan topikal yang efektif bagi pengobatan jerawat.